The Spectral Irradiance, Growth, Photosynthetic Characteristics, Antioxidant System, and Nutritional Status of Green Onion (Allium fistulosum L.) Grown Under Different Photo-Selective Nets - Gao, Song; Liu, Xuena; Liu, Ying; Cao, Bili; Chen, Zijing; Xu, Kun (Frontiers in Plant Science, 2021)
Active regulation of the plant growth environment is a common method for optimizing plant yield and quality. In horticulture today, light quality control is carried out using photo-selective nets or membranes in order to improve the yield and quality of cultivated plants. In the present study, with natural light as control (CK), we tested different photo-selective nets (white, WN; blue, BN; green, GN; yellow, YN; and red, RN) with 30% shade on the growth, development, quality, yield, photosynthesis, chlorophyll fluorescence characteristics, and antioxidant system, as well as the influence of element absorption and transformation of green onion (Allium fistulosum L.) plants at different growth stages. We found that plants under BN and WN have greater height and fresh weight than those of plants under the other nets. Plants under the BN treatment had the highest quality, yield, photosynthetic pigment content, net photosynthetic rate, transpiration rate, and stomatal conductance, whereas the intercellular CO2 concentration was the highest in plants in the YN treatment. The photosynthesis noon break phenomenon was significantly lower in plants covered photo-selective nets than in CK plants. NPQ was the highest in the YN treatment, and Fv/Fm, ΦPSII and qP among the plants in the other treatments were different; from highest to lowest, they were as follows: BN>WN>CK>RN>GN>YN. The active oxygen content of green onion leaves in the BN treatment was significantly lower than that in the other treatments, and their key enzyme activity was significantly increased. BN also improved the absorption and transformation of elements in various organs of green onion.